Managing Indian Railways - Agarwal, V. K. (New Delhi, 2004)
Indian Railways (IR) is the second largest railway sytem of the world and its vast network has a route kilometrage of 63,000 Km. About 14,400 trains are run daily on the network carrying 14 million passengers and 1.4 million tonnes of freight.
Keywords: Railways-India